A review on remanufacture of dies and moulds - Chen, Changrong; Wang, Yan; Ou, Hengan; He, Yan; Tang, Xianzhi (Elsevier, 2014)
Dies and moulds, which are essential tools for manufacturing engineered products, usually fail or become obsolete after a certain period of use for a variety of reasons. Thus, they often need remanufacture. The objectives of this paper are to review the current state of the art in remanufacture of dies and moulds and to investigate the potential benefits and opportunities associated with remanufacturing. In this paper, the benefits of introducing remanufacture into the die and mould industry are firstly discussed. This is followed by a summary of the unique characteristics of remanufacturing of dies and moulds compared to those of other products. Industrial repair strategies of the main types of dies and moulds are examined. Key technologies needed for remanufacture are then reviewed in detail including welding repair technologies, remaining useful life evaluation methods, and reliability analysis. Finally, challenges and opportunities facing the industry and academia are discussed in order to draw several key conclusions.